High specific surface area anti-poisoning blast furnace gas hydrolysis catalyst and preparation method thereof

By using γ-Al2O3 carrier, alkali metal active ingredients, rare earth metal additives and pore reamers in blast furnace gas COS hydrolysis catalyst, combined with specific preparation methods, the problems of short catalyst life and fast inactivation are solved, and efficient and long-life blast furnace gas hydrolysis catalytic effect is achieved.

CN114471522BActive Publication Date: 2025-04-01SOUTHEAST UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111669164.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-04-01
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The existing blast furnace gas COS hydrolysis catalyst has a short life and fast inactivation, and has significant adsorption during purification, making it difficult to promote and apply.

Method used

Using γ-Al2O3 as the support, alkali metal as the active ingredient, and rare earth metal as the auxiliary agent, a catalyst for adding a pore reamer is prepared through specific preparation methods, including dissolution and mixing, ultrasonic stirring, drying and calcining, a blast furnace gas hydrolysis catalyst with high specific surface area resistance is prepared.

Benefits of technology

The catalyst has achieved high desulfurization efficiency and long life, and can achieve 100% desulfurization efficiency under 75°C, and the outlet H2S selectivity reaches 100%, without adsorption, deposition, oxidation and other problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114471522B_ABST
    Figure CN114471522B_ABST
Patent Text Reader

Abstract

The present invention discloses a high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst and a preparation method thereof. The catalyst uses γ-alumina as a carrier, alkali metal oxide as an active ingredient, and rare earth metal oxide as an auxiliary agent. A variety of pore-forming agents are added during the preparation process. The preparation method comprises dissolving an aluminum precursor, an alkali precursor, a rare earth metal precursor, and a pore-enlarging agent in deionized water and stirring evenly, adding ammonia water in batches and slowly during ultrasonic stirring to adjust the pH until precipitation is complete, and then standing, heating and stirring, drying, grinding, and calcining to obtain a COS hydrolysis catalyst. The advantages are that the COS hydrolysis catalyst prepared by adding a pore-enlarging agent, a rare earth metal, and an alkali metal has a high specific surface area and a more macroporous structure, and can achieve a high COS hydrolysis conversion rate and H at 75°C. 2 S yield and long life; at the same time, the preparation method of the invention is simple and easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of blast furnace gas hydrolysis catalysis, and in particular relates to a high specific surface area, low temperature and poisoning resistant blast furnace gas COS hydrolysis catalyst and a preparation method thereof. Background Art

[0002] With the promulgation of the "Opinions on Promoting the Implementation of Ultra-low Emissions in the Steel Industry" and other regulations, the steel industry has officially entered the ultra-low emission transformation stage. The regulations clearly state that the concentration of hydrogen sulfide (H2S) in blast furnace gas of steel enterprises should be ≤20mg / Nm 3 Monitoring statistics show that inorganic sulfur in blast furnace gas is mostly hydrogen sulfide, accounting for about 30%, and organic sulfur is mainly carbonyl sulfide (COS), accounting for about 70%, and there is a trace amount of carbon disulfide (CS2). The removal of organic sulfur is the main difficulty.

[0003] The hydrolysis catalytic method has become the best blast furnace gas desulfurization technology at present due to its mild reaction conditions, high desulfurization efficiency and no by-products.

[0004] At present, the research on catalysts mainly focuses on two types: metal oxide-based and non-metal-based.

[0005] Metal oxide-based hydrolysis catalysts are mainly based on metal oxides represented by γ-Al2O3 and TiO2, and non-metallic catalysts are mainly carbon-based catalysts.

[0006] Existing catalysts have a short lifespan, deactivate quickly, and have significant adsorption effects during the purification process, making them difficult to truly promote and apply.

[0007] For example, patent CN112058273A discloses an activated carbon-based catalyst, the core of which is that the activated carbon-based catalyst is loaded with one or more of zinc oxide, iron oxide, manganese oxide, and copper oxide as active components, and alkali metal or alkaline earth metal oxides are used as co-catalysts to improve the catalytic efficiency of the catalyst. However, the desulfurization mechanism of the catalyst is mainly adsorption oxidation. When the activated carbon reaches adsorption saturation, the desulfurization efficiency will drop rapidly.

[0008] Therefore, the research and development of a COS hydrolysis catalyst with high desulfurization efficiency, long life and simple preparation technology has become a hot topic in the research field of this technology and is of great significance to the fine desulfurization of blast furnace gas. Summary of the invention

[0009] The purpose of the present invention is to solve the problems of the prior art, to provide a blast furnace gas COS hydrolysis catalyst with high desulfurization efficiency and long service life, and to provide a method for preparing the catalyst.

[0010] The specific technical scheme of the present invention is as follows: the catalyst of the present invention uses γ-Al2O3 as a carrier, alkali metal as an active ingredient, rare earth metal as an auxiliary agent, and a pore expander; the mass ratios of alkali metal, rare earth metal, pore expander and carrier in the catalyst are (0.03-0.15): (0.001-0.010): (0.05-0.20): 1 respectively;

[0011] Furthermore, the alkali metal in the catalyst is one or more of Na, K and Ca.

[0012] Furthermore, the pore expanding agent in the catalyst is one or more of polyvinyl alcohol, polyacrylamide, and dodecylbenzene sulfonic acid; the precursor of the carrier is Al(NO3)3, and the precursor of the catalyst active component is one or more of K2CO3, CH3COOK, Na2CO3, CH3COONa, and Ca(CH3COO)2; the rare earth metal in the catalyst is one or more of holmium, neodymium, and lanthanum, and the precursor is one or more of nitrate, acetate, and oxalate.

[0013] The present invention also discloses a method for preparing a high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst, comprising the following steps:

[0014] Step 1, weighing the precursor of the carrier, the precursor of the alkali metal, the precursor of the rare earth metal and the pore-enlarging agent according to the mass ratio of the alkali metal, the rare earth metal, the pore-enlarging agent and the carrier in the catalyst respectively in the mass ratio of (0.03-0.15): (0.001-0.010): (0.05-0.20): 1, dissolving them in deionized water, stirring and mixing them well to form an emulsion to be processed;

[0015] Step 2: Under ultrasonic stirring conditions, NH3·H2O is slowly added in batches to adjust the pH to 8-10. The obtained emulsion is sequentially subjected to standing at room temperature, stirring at elevated temperature, drying, grinding and calcining to obtain a high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst.

[0016] Furthermore, in the step 1, the order of dissolving and mixing the catalyst is to first add the precursor of the carrier and the precursor of the alkali metal, stir them sufficiently for reaction, then add the precursor of the rare earth metal, and finally add the pore expander.

[0017] Furthermore, in the step 2, the ultrasonic frequency of the ultrasonic stirring is 80 to 120 kHz.

[0018] Furthermore, in the step 2, NH3·H2O solution is added to the emulsion to be processed in 3-5 times until the pH of the emulsion to be processed reaches 8-10; after each addition of NH3·H2O solution, ultrasonic stirring is performed for 10-15 minutes until the solution becomes clear again or the precipitate is evenly dispersed.

[0019] Furthermore, in the step 2, the standing at room temperature is specifically standing at 35-50°C for 16-24h; the heating stirring is specifically heating stirring for 5h, the stirring speed is 40-50r / s, and the temperature is 60-80°C.

[0020] Furthermore, in the step 2, the drying process includes: drying at 100°C to 120°C for 22 to 26 hours, and then continuing to dry at 140 to 160°C for 10 to 12 hours.

[0021] Furthermore, in the step 2, the calcination includes: calcining at 300-400° C. for 1-2 hours, and then calcining at 600-750° C. for 4-6 hours.

[0022] Compared with the prior art, the present invention has the following significant advantages:

[0023] 1. The preparation method of the present invention is simple and easy to operate. Before chemical precipitation, an appropriate amount of preferred pore-enlarging agent and carbonate or nitrate of an active auxiliary agent is added so that the additive is evenly wrapped in the precipitated particles during the addition of ammonia water; a large amount of gas is decomposed and released during the drying and calcination process, and the pore structure of the catalyst is improved from the inside to achieve a pore-forming effect. Therefore, the specific surface area of ​​the prepared catalyst is significantly increased, and the proportion of macropores is significantly increased, which is conducive to the adsorption of COS and the timely overflow of H2S, avoiding the retention and oxidation of H2S inside the pores, reducing the deposition of sulfur and sulfate, and making the catalyst more active and more anti-poisoning. Experiments have shown that the high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst can achieve a desulfurization efficiency of 100% at 75°C, and the H2S selectivity at the outlet reaches 100%, that is, all COS is converted into H2S without adsorption, deposition, oxidation, etc.

[0024] 2. In the catalyst, the doping of rare earth elements adds more reactive active sites. The interaction between alkali metals and rare earth elements effectively promotes the low-temperature hydrolysis activity of the catalyst and reduces the activation temperature.

[0025] 3. Control the order of adding raw materials, prepare the emulsion to be processed, first add the precursor of the carrier and the precursor of the alkali metal, stir the reaction sufficiently, then add the precursor of the rare earth metal, and finally add the pore expander; secondly, in the process of adding ammonia water, add it in batches and use ultrasonic mixing to effectively avoid local flocculation caused by adding ammonia water too quickly, thereby ensuring uniform preparation of the catalyst and good catalytic effect.

[0026] 4. In the present invention, drying is first carried out at about 100°C for 24 hours to fully dehydrate the sample; then drying is carried out at about 160°C for 12 hours, at which temperature, the added additives such as polyvinyl alcohol are fully dehydrated and etherified; calcination is first carried out at 300-400°C for 1-2 hours, at which time additives such as active additives and pore expanders are gradually decomposed, and then the temperature is raised to 600°C-750°C for further calcination; this method is based on a drying and calcination process that matches the characteristics of precursors and additives, which maximizes the improvement effect of the additives on activity and anti-poisoning performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is the desulfurization performance curve of the hydrolysis catalyst of the present invention;

[0028] Figure 2 is a long-term deterioration curve of the hydrolysis catalyst of the present invention;

[0029] Figure 3 It is the pore size distribution curve of the hydrolysis catalyst of the present invention. DETAILED DESCRIPTION

[0030] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with the accompanying drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The raw materials used in the present invention can all be purchased from the market.

[0031] Comparative Example 1

[0032] The catalyst was commercial γAl2O3 without any treatment or modification.

[0033] Example 1

[0034] The catalyst raw materials are: 5g aluminum nitrate, 0.036g polyvinyl alcohol, 0.043g holmium nitrate, and 0.216 potassium carbonate.

[0035] Preparation process:

[0036] First, aluminum nitrate, potassium carbonate and holmium nitrate were dissolved in 50 mL of deionized water, polyvinyl alcohol was added, and the mixture was stirred until completely dissolved; then, 5 ml of ammonia water was slowly added under ultrasonic conditions of 80 kHz, and ultrasonication was performed for 10 minutes. After the solution was uniform, 5 ml of ammonia water was added again, and the operation was repeated until the pH reached 10. The obtained emulsion was allowed to stand at 40°C for 24 hours, stirred at 60°C for 4 hours at a speed of 60 r / min in a magnetic stirrer, dried in an oven at 110°C for 24 hours, taken out and ground to less than 100 mesh, and calcined at 700°C in a muffle furnace for 6 hours to obtain a hydrolysis catalyst with a mass ratio of polyvinyl alcohol, Ho, K and Al2O3 of 0.05:0.001:0.05:1.

[0037] Example 2

[0038] The catalyst raw materials are: 5g titanium dioxide, 0.072g polyacrylamide, 0.214g neodymium nitrate and 0.562g sodium carbonate.

[0039] First, aluminum nitrate, sodium carbonate and neodymium nitrate were dissolved in 50 mL of deionized water, polyacrylamide was added, and the mixture was stirred until completely dissolved; then, 10 ml of ammonia water was slowly added under ultrasonic conditions of 100 kHz, and ultrasonication was performed for 8 minutes. After the solution was uniform, 10 ml of ammonia water was added again, and the operation was repeated until the pH reached 10. The obtained emulsion was allowed to stand at 50°C for 24 hours, stirred at 70°C for 4 hours at a speed of 60 r / min in a magnetic stirrer, dried in an oven at 120°C for 24 hours, taken out and ground to less than 100 mesh, and calcined at 650°C in a muffle furnace for 6 hours to obtain a hydrolysis catalyst with a mass ratio of polyacrylamide, Nd, Na and Al2O3 of 0.10:0.005:0.10:1.

[0040] Example 3

[0041] The preparation steps are the same as those in Example 1, except that the catalyst raw materials are: 5 g titanium dioxide, 0.036 g dodecylbenzenesulfonic acid, 0.212 g lanthanum nitrate and 0.806 g calcium acetate.

[0042] The prepared catalyst is a hydrolysis catalyst in which the mass ratio of dodecylbenzenesulfonic acid, La, Ca and Al2O3 is 0.05:0.005:0.15:1.

[0043] Example 4

[0044] The preparation steps are the same as those in Example 1, except that the catalyst raw materials are: 5 g titanium dioxide, 0.108 g polyacrylamide and 0.153 g potassium acetate.

[0045] The prepared catalyst is a hydrolysis catalyst with a mass ratio of polyacrylamide, K and Al2O3 of 0.15:0.05:1.

[0046] Test Example 1

[0047] The catalysts prepared in Comparative Example 1 and Examples 1-4 were ground, tableted, and sieved, and 0.5 ml of 40-60 mesh samples were taken for catalytic activity test experiments. The test temperature range was 50-150°C. The experiment used cylinder gas to simulate blast furnace gas, in which the volume fractions of COS and O2 were 0.02% and 1% respectively, N2 was used as the carrier gas, the total gas flow rate was set to 200 ml / min, and the space velocity (GHSV) was 24000 h -1 Before the mixed gas passes through the reaction tube, it first passes through a first-stage gas washing bottle filled with 50 ml of pure water to achieve the introduction of H2O. The concentrations of COS and H2S are measured by GC-9860 gas chromatograph (Haoerpu, China), and SO2 is detected by 350-XL flue gas analyzer (Testo, Germany). The analysis results are shown in Figure 1 .

[0048] Depend on Figure 1 It can be seen that, first, when Comparative Example 1 is used as a hydrolysis catalyst, the COS removal rate is less than 50% at 75°C, and the H2S selectivity is 19%; at 150°C, the COS removal rate is close to 100%.

[0049] Second, the high specific surface area low temperature anti-poisoning hydrolysis catalyst prepared in Example 1; at 75°C, the COS removal rate is 80.53%, and the H2S selectivity is 41%; in the temperature range of 100-150°C, the COS removal rate is above 90%, and the H2S selectivity is above 80%;

[0050] Third, the high specific surface area low temperature anti-poisoning hydrolysis catalyst prepared in Example 2; at 75°C, the COS removal rate is 95.8%, and the H2S selectivity is 85%; in the temperature range of 100-150°C, the COS removal rate is above 95%, and the H2S selectivity is above 90%;

[0051] Fourth, the high specific surface area low temperature anti-poisoning hydrolysis catalyst prepared in Example 3; at 75°C, the COS removal rate is 97.23%, and the H2S selectivity is 91%; in the temperature range of 100-150°C, the COS removal rate is above 95%, and the H2S selectivity is above 95%;

[0052] Fifth, the high specific surface area low temperature anti-poisoning hydrolysis catalyst prepared in Example 4; at 75°C, the COS removal rate is 80.24%, and the H2S selectivity is 53%; in the temperature range of 100-150°C, the COS removal rate is above 95%, and the H2S selectivity is above 90%;

[0053] In summary, the denitration catalyst prepared by the present invention has a lower activation temperature and a wider active temperature window. The high specific surface area, low temperature and anti-poisoning hydrolysis catalysts prepared in Examples 1-4 can achieve a denitration efficiency of more than 80% between 75°C and 150°C.

[0054] Test Example 2

[0055] Test Example 2 The catalyst prepared in Example 1 was subjected to a long-term deterioration test. The test conditions were the same as those in Test Example 1. The test results were as follows: Figure 2 ;Depend on Figure 2 It can be seen that the hydrolysis catalyst prepared by the invention has strong anti-poisoning ability and long life. After 110 hours of experiments, the COS removal rate of the catalyst is still stable at more than 90%, and the outlet H2S selectivity is maintained at more than 80%, which proves that the catalyst prepared by the invention has low-temperature, high-efficiency and anti-poisoning capabilities.

[0056] The catalysts prepared in Examples 1-4 were subjected to BET surface area tests using commercial alumina as a comparison. The pore size distribution results are shown in Table 1. Figure 3 The BET specific surface area results are shown in Table 1.

[0057] Depend on Figure 3 It can be seen that the pore size of Comparative Example 1 is mainly mesopores less than 4 nm, and the pore size distribution is relatively concentrated.

[0058] The hydrolysis catalyst prepared by the invention, taking Example 3 as an example, has a pore size distribution in the range of 5-18 nm, a wider pore size distribution, and more macroporous structures. More macroporous structures enhance the diffusion of COS and H2S gases, which on the one hand promotes the improvement of hydrolysis activity, and on the other hand, faster diffusion of H2S will reduce sulfur deposition and further oxidation, thereby achieving improved anti-poisoning performance. It is proved that the catalyst prepared by this method has a wider pore size distribution and more macroporous structures.

[0059] Table 1 Catalyst BET specific surface area test results

[0060]

[0061] Depend on Figure 3 It can be concluded from the test results in Table 1 that the catalyst has a higher specific surface area than conventional alumina by 10.6-18%. The higher specific surface area and more macroporous structures promote the catalyst to achieve higher catalytic activity and stronger anti-poisoning ability.

[0062] The above specific implementation methods are only for illustrating the technical concept and structural features of the present invention, and the purpose is to enable relevant persons familiar with this technology to implement it. However, the above content does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should fall within the protection scope of the present invention.

Claims

1. A high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst, characterized in that: The catalyst uses γ-Al2O3 as a carrier, alkali metal as an active ingredient, rare earth metal as an auxiliary agent, and a pore expander; wherein the mass ratios of the alkali metal, rare earth metal, pore expander and carrier in the catalyst are (0.03-0.15): (0.001-0.010): (0.05-0.20): 1 respectively; The pore-enlarging agent in the catalyst is one or more of polyvinyl alcohol, polyacrylamide, and dodecylbenzene sulfonic acid; the precursor of the carrier is Al(NO3)3, and the precursor of the catalyst active component is one or more of K2CO3, CH3COOK, Na2CO3, CH3COONa, and Ca(CH3COO)2; the rare earth metal in the catalyst is one or more of holmium, neodymium, and lanthanum, and the precursor is one or more of nitrate, acetate, and oxalate; The preparation method of the high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst comprises the following steps: Step 1, weighing the precursor of the carrier, the precursor of the alkali metal, the precursor of the rare earth metal and the pore-enlarging agent respectively according to the mass ratio of the elements of the alkali metal, the rare earth metal, the pore-enlarging agent and the carrier in the catalyst in the mass ratio of (0.03-0.15): (0.001-0.010): (0.05-0.20): 1, dissolving them in deionized water, stirring and mixing them evenly to form an emulsion to be processed; the order of dissolving and mixing the catalyst is to first add the precursor of the carrier and the precursor of the alkali metal, stir the reaction sufficiently, then add the precursor of the rare earth metal, and finally add the pore-enlarging agent; Step 2: Under ultrasonic stirring conditions, NH3·H2O is slowly added in batches to adjust the pH to 8-10, and the obtained emulsion is sequentially subjected to standing at room temperature, stirring at elevated temperature, drying, grinding and calcining to obtain a high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst; the NH3·H2O solution is added to the emulsion to be processed in 3-5 times until the pH of the emulsion to be processed reaches 8-10; after each addition of the NH3·H2O solution, ultrasonic stirring is performed for 10-15 minutes until the solution is clarified again or the precipitate is evenly dispersed; The drying process includes: drying at 100°C to 120°C for 22 to 26 hours, and then continuing to dry at 140 to 160°C for 10 to 12 hours; The calcination comprises: calcining at 300-400° C. for 1-2 hours, and then calcining at 600-750° C. for 4-6 hours.

2. A method for preparing the high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst according to claim 1, characterized in that: The steps include: Step 1, weighing the precursor of the carrier, the precursor of the alkali metal, the precursor of the rare earth metal and the pore-enlarging agent respectively according to the mass ratio of the elements of the alkali metal, the rare earth metal, the pore-enlarging agent and the carrier in the catalyst in the mass ratio of (0.03-0.15): (0.001-0.010): (0.05-0.20): 1, dissolving them in deionized water, stirring and mixing them evenly to form an emulsion to be processed; the order of dissolving and mixing the catalyst is to first add the precursor of the carrier and the precursor of the alkali metal, stir the reaction sufficiently, then add the precursor of the rare earth metal, and finally add the pore-enlarging agent; Step 2: Under ultrasonic stirring conditions, NH3·H2O is slowly added in batches to adjust the pH to 8-10, and the obtained emulsion is sequentially subjected to standing at room temperature, stirring at elevated temperature, drying, grinding and calcining to obtain a high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst; the NH3·H2O solution is added to the emulsion to be processed in 3-5 times until the pH of the emulsion to be processed reaches 8-10; after each addition of the NH3·H2O solution, ultrasonic stirring is performed for 10-15 minutes until the solution is clarified again or the precipitate is evenly dispersed; The drying process includes: drying at 100°C to 120°C for 22 to 26 hours, and then continuing to dry at 140 to 160°C for 10 to 12 hours; The calcination comprises: calcining at 300-400° C. for 1-2 hours, and then calcining at 600-750° C. for 4-6 hours.

3. The method for preparing the high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst according to claim 2, characterized in that: In the step 2, the ultrasonic frequency of the ultrasonic stirring is 80 to 120 kHz.

4. The method for preparing the high specific surface area anti-poisoning blast furnace gas hydrolysis catalyst according to claim 2, characterized in that: In the step 2, the normal temperature standing is specifically standing at 35-50°C for 16-24h; the heating stirring is specifically heating stirring for 5h, the stirring speed is 40-50r / s, and the temperature is 60-80°C.

Citation Information

Patent Citations

  • Catalyst for hydrolysis of carbonyl sulfide as well as preparation method and application thereof

    CN106031868A